Evaluation for education program and basic training for Jakarta public order agency - urkanus sihombing; Hamidah; Billy Tunas (Program Studi S3 Ilmu Manajemen, 2020)
This research/evaluation be held for evaluating Evaluation for education program and basic training for Jakarta public order agency in periode 2012 until 2018 which be held by Civil service police and Human Resources Development Agency (Field Study). This evaluation for analising comprehensively to significant several aspect in several stages, which consists of stages1, including aspect : a. Legal foundation, b. Need analysis, c. Purpose, also program targets, and stages2, including aspect: a. Participant, b. Organization structure, c. Program and activities, d. Procedure, e.Guidebook, f. Instructors, g. Administrator/Committee, h. Instructional media, i. Means, infrastructure, and Budget, and stages3, including aspect, a. Participant reaction, b. Learning, c. Behavior, also stages4, which including: a.result, b. Program impact. Qualitative approach used on this research. Primary data, and secunder was obtained through observation, interview, study of document, focus group discussion, with all the credible informants. This evaluation be held by using Stufflebeam model, Context, Input, Process and Product (CIPP). Data analysis trough interactive approach Miles and Huberman in data display activity, data reduction, and drawing conclusion. Research/evaluation result. Evaluation result showing that most aspects in contex stages, input, and process also product, getting good judgment, Which means it's done / available according to criteria, so program recommended need to be developed with adjustment on law No.23 of 2014 about local government and Government regulation No. 16 of 2018 about civil service police which has become the development guidelines of education basic program, technical, and functional civil service police all over Indonesia.